2011
DOI: 10.1177/147323001103900546
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Acquired Aplastic Anaemia in Adults: 142 Cases from a Multicentre, Prospective Cohort Study in Shanghai, China

Abstract: To improve diagnosis and therapy for aplastic anaemia (AA) in Shanghai, clinical and laboratory data for patients with AA (n = 142) and hypocellular myelodysplastic syndrome (MDS; n = 22) were comparatively analysed (follow-up 2 -6 years). Red blood cell distribution width and absolute lymphocyte and reticulocyte counts were significantly different between the two groups. AA was diagnosed in 54.2% of patients using a single bone marrow aspirate smear plus peripheral haemogram results, and in 95.1% using an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Survival rates have been reported as high as 85-90%. Wang W et al has reported 74.1% [16] while Eapen M et al [17] have reported an overall survival of 76% by using bone marrow only as a source of stem cells. In our group of patients, bone marrow as well as peripheral blood was used as a combination for the source of stem cells with 71% survival which is equivalent to international literature.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates have been reported as high as 85-90%. Wang W et al has reported 74.1% [16] while Eapen M et al [17] have reported an overall survival of 76% by using bone marrow only as a source of stem cells. In our group of patients, bone marrow as well as peripheral blood was used as a combination for the source of stem cells with 71% survival which is equivalent to international literature.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is evidence-based and supported by 6 studies, [22][23][24][25][26][27] all of which met the inclusion criteria for the systematic review. These 6 studies comprise 2 prospective cohort studies (PCSs) 22,26 and 4 RCSs.…”
Section: Guideline Statementsmentioning
confidence: 95%
“…Four studies, comprising 1 PCS 22 and 3 RCSs, 24,25,27 reported clinical significance for data on platelets in MDS, myeloproliferative disease, adult T-cell leukemia/lymphoma patients. Two RCSs 24,27 reported clinical significance for data on absolute neutrophil count in patients with AA, and 1 RCS 26 reported clinical significance for data on reticulocyte count and red cell distribution width in patients with AA and MDS. Refer to Table 5 for study data by outcome of significance for peripheral blood specimens.…”
Section: Guideline Statementsmentioning
confidence: 99%
See 2 more Smart Citations